Apocalypse Now? Hoa Hao Buddhism Emerging from the Shadows of War - Taylor, Philip (The Australian journal of anthropology, 2001)
Hoa Hao Buddhism, founded in the late French colonial era is, like the other religions of ethnic Vietnamese in the Mekong delta, an eclectic and creative approach to imagining existence in this newly settled region. This paper investigates the context in which this faith evolved and explores its main characteristics. These include its settler colonialist worldview, synthesis of diverse cultural currents, universalist outlook and construction of a moral community. It concludes by exploring the religion's contemporary relevance, uneasy relationship with the state and the perceived challenges faced as the integration of the delta into broader economic and cultural structures continues.